Comparison of Visual Evoked Potentials and Retinal Nerve Fiber Layer Thickness in Alzheimer’s Disease - Kromer, Robert; Serbecic, Nermin; Hausner, Lucrezia; Froelich, Lutz; Beutelspacher, Sven C. (Frontiers in Neurology, 2013)
Introduction Alzheimer‘s disease is a long term progressive neurodegenerative disease and might affect the retinal nerve fibre layer thickness of the eye. There is increasing evidence that visual evoked potentials, which are an objective way to indicate visual field loss, might be affected by the disease as well. Material and Methods 22 patients (mean age: 75.9 ± 6.1 years; 14 women) with mild-to-moderate Alzheimer‘s disease and 22 sex-matched healthy patients were examined. We compared the use of visual evoked potentials and retinal nerve fibre layer thickness using latest high-resolution spectral domain optical coherence tomography with eye-tracking capabilities for optimised peripapillary scan centring for the first time in Alzheimer‘s disease patients. Results The mean MMSE score was 22.59 ± 5.47 in the Alzheimer‘s disease group, and did not significantly correlate with the visual evoked potentials latencies. We found no significant difference between the visual evoked potentials latencies of the Alzheimer‘s disease patients and those of the control patients. No peripapillary sector of the retina had a retinal nerve fibre layer thickness significantly correlated with the visual evoked potentials latencies. Discussion We demonstrated that pattern visual evoked potentials did not show any significant correlation despite subtle loss in retinal nerve fibre layer thickness. It remains open whether additional flash visual evoked potentials combined with retinal nerve fibre layer thickness analysis may be useful in diagnosing Alzheimer‘s disease, particularly for mild-to-moderate stages of the disease.